Of pain and penises deconstructing hegemonic masculinity in the Ultimate Fighting Championship fights - Berame, Janyn Payas 1993-; Enriquez, Elizabeth L., Ph.D.; University of the Philippines. College of Mass Communication (2014)
"the study uses textual analysis to read how masculinities are expressed and articulated in the Ultimate Fighting Championship (UFC) maincard bouts, and how these expression relate on the concept of hegemonic masculinity. Sports the rely on body-contact confrontations are viewed as an unrelenting renewal of the manhood, an affirmation of hegemonic masculinity, which is problematic, since the physical intimacy of the sport opens discourses of homosexuality and homoeroticism. The study indorporates poststructuralist perspective, mainly of Derridean deconstruction to produce an understanding of hegemonic masculinity's articulation and operation inside UFC. By studying and applying the different ideas and concepts of deconstruction on how hegemonic and subordinate masculinities are expressed and articulated, the study wishes to discuss the following: the relationship and politics of hegemonic masculinity and subordinate masculinities, and how the expressions of these masculinities rely on the very ideas and concepts that they reject - fear, anxiety, homoeroticism and feminity, based on the textual analysis of the UFC maincard fights."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Ultimate Fighting Championship (Organization).; Masculinity in sports